(untitled) (Research, Society and Development, 2023)
Background: Benign Paroxysmal Positional Vertigo (BPPV) is one of the most frequent pathologies of the vestibular system. The treatment maneuvers involve changes in the position of the head, as proposed by previous research. The objective of this research was to describe a new otolith repositioning maneuver in supine position for patients diagnosed with posterior canal BPPV due to canalithiasis. Methods: we described a new otolith repositioning maneuver that does not involve a change of position in decubitus, being performed in the supine to sitting position. This is an uncontrolled clinical study to evaluate the effects of maneuver after 1 hour and after 1 week. Results: The present study obtained a success rate (abolition of nystagmus and positional vertigo) in 85.19% of patients after a single application of the new maneuver presented and in a further 9.26% after two maneuvers, totaling 94.44% success rate with 1 or 2 maneuvers performed on the same day. Conclusions: The new maneuver studied eliminated nystagmus and positional vertigo in most patients with PC BPPV. It may be preferred for patients who have difficulties in performing maneuvers that involve changing body position on the narrow stretcher and the execution of the lateral decubitus position.